Education Quality Management: Communication Management and the Principal Strategy in Improving the Quality of Education at SMPN Medan - Simarmata, Bengettua (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
When it comes to raising the bar for student learning, the two most important variables are influential communication management and the tactics used by school leaders. A qualitative descriptive technique is used in this study. Data is gathered via interviews, documentary studies, and observation. First, the principal kept everyone in the loop regarding quality improvement management strategies and plans. Second, the principal ensured that teachers had plenty of chances to participate in quality planning, work with committees to create school budgets, become more competent educators, follow the curriculum, and get help and advice when needed. Third, the principal's approach to quality improvement guided the school's learning and teaching through group and individual strategies. Lastly, the principal directed and controlled the school by setting quality policies, objectives, plans, and procedures and ensuring their ongoing success. Stakeholder satisfaction and ever-improving educational quality are the end goals of quality management, which seeks to guarantee process and product conformance.